Dietary Flaxseed Oil Protects against Bleomycin-Induced Pulmonary Fibrosis in Rats - Joshua Lawrenz; Betty Herndon; Afrin Kamal; Aaron Mehrer; Daniel C. Dim; Cletus Baidoo; David Gasper; Jonathan Nitz; Agostino Molteni; Richard C. Baybutt (Pulmonary Medicine)
Bleomycin, a widely used antineoplastic agent, has been associated with severe pulmonary toxicity, primarily fibrosis. Previous work has shown a reduction in bleomycin-induced lung pathology by long-chain omega-3 fatty acids. Treatment by short-chain omega-3 fatty acids, α-linolenic acid, found in dietary flaxseed oil may also reduce lung fibrosis, as previously evidenced in the kidney. To test this hypothesis, 72 rats were divided between diets receiving either 15% (w/w) flaxseed oil or 15% (w/w) corn oil (control). These groups were further divided to receive either bleomycin or vehicle (saline) via an oropharyngeal delivery, rather than the traditional intratracheal instillation. Lungs were harvested at 2, 7, and 21 days after bleomycin or saline treatment. Animals receiving flaxseed oil showed a delay in edema formation (𝑃=0.025) and a decrease in inflammatory cell infiltrate and vasculitis (𝑃=0.04 and 0.007, resp.). At days 7 and 21, bleomycin produced a reduction in pulmonary arterial lumen patency (𝑃=0.01), but not in rats that were treated with flaxseed oil. Bleomycin-treated rats receiving flaxseed oil had reduced pulmonary septal thickness (𝑃=0.01), signifying decreased fibrosis. Dietary flaxseed oil may prove beneficial against the side effects of this highly effective chemotherapeutic agent and its known toxic effects on the lung.